PEDAGOGICAL PECULIARITIES OF FORMING LINGUOCULTURAL COMPETENCE OF HIGHER EDUCATION STUDENTS IN KARAKALPAKSTAN - Zoya Sarsenbaeva Jangabay qizi, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article deals with the pedagogical importance and peculiarities of linguocultural competence and ways of forming linguocultural competence of higher education students in Karakalpakstan. The article gives students a clear explanation of the linguocultural competence and its interactions throughout its development, and improving linguocultural competence with the help of materials in the English and Karakalpak languages. In the article, empirical, qualitative, comparative, and semantic methods analyses have been used. Furthermore, interviews for the research problem were based upon fifteen questions and questionnaires were administered and interviews were conducted. The author notes that through learning national proverbs based on a comparative analysis, students will be able to learn national and foreign culture, and develop linguocultural competence as well.